2006
DOI: 10.1002/app.24641
|View full text |Cite
|
Sign up to set email alerts
|

Rheological investigation of microphase separation transition of polyurethane elastomer

Abstract: A technique of linear viscoelasticity measurements coupling with temperature scanning was found effective in the detection of microphase separation transition (MST) and in the determination of MST temperature. The validity and accuracy of the technique were confirmed and reinforced by atomic force microscopy and differential scanning calorimetry (DSC). The technique was applied to a study of the MST of a series of 13 polyurethane (PU) elastomers based on mixed toluene diisocyanate (TDI), 1,4 butadiol, and poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…As a whole, we observed that the values of G 0 and G 0 0 both increased with increasing o, but decreased upon increasing the temperature. Such a result was in qualitative agreement with the findings from related experiments by Yang et al, 78 who adopted atomic force microscopy (AMF) and differential scanning calorimetry (DSC) to investigate the linear viscoelasticity measurements and detected the microphase separation transition for polyurethane (PU) elastomer. Surprisingly, at higher frequencies (o > 6.28 Â 10 11 rad s À1 ), all of the G 0 0 (o) curves closely matched each other, demonstrating the temperature independence of G 0 0 .…”
Section: Temperature Dependencesupporting
confidence: 90%
“…As a whole, we observed that the values of G 0 and G 0 0 both increased with increasing o, but decreased upon increasing the temperature. Such a result was in qualitative agreement with the findings from related experiments by Yang et al, 78 who adopted atomic force microscopy (AMF) and differential scanning calorimetry (DSC) to investigate the linear viscoelasticity measurements and detected the microphase separation transition for polyurethane (PU) elastomer. Surprisingly, at higher frequencies (o > 6.28 Â 10 11 rad s À1 ), all of the G 0 0 (o) curves closely matched each other, demonstrating the temperature independence of G 0 0 .…”
Section: Temperature Dependencesupporting
confidence: 90%
“…Also, the shear rate versus shear stress curves give an idea about the flow behavior of the material under processing conditions. From these data, information about the macromolecular packing, crystallinity as well as a pattern of H‐bondings can be obtained 52–54 . The measurements of the solid samples were carried out at RT by varying the shear rate in the range of 0–100 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…From these data, information about the macromolecular packing, crystallinity as well as a pattern of H-bondings can be obtained. [52][53][54] The measurements of the solid samples were carried out at RT by varying the T A B L E 3 DSC analysis data of as-synthesized hard segments of PUs with different lengths of chain extenders.…”
Section: Rheological Studiesmentioning
confidence: 99%
“…In our another study, 119 the microphase separation, cross‐linking density (CLD), and mechanical properties of PU‐Fe 3 O 4 composites prepared through in situ polymerization were studied. We found that a small amount of nano‐Fe 3 O 4 can greatly improve the CLD.…”
Section: Effect Of Filler On Microphase Separation and Mechanical Pro...mentioning
confidence: 99%
“…Schematic representation for microphase separation of (A) pristine polyurethane (PU); (B, C) PU nanocomposites filled with low and high Fe 3 O 4 contents (reproduced with permission from Reference 119). HD, hard microdomains.…”
Section: Effect Of Filler On Microphase Separation and Mechanical Pro...mentioning
confidence: 99%